Aesthetic-functional rehabilitation of deciduous anterior teeth without removal of carious tissue: series of clinical cases - Alessandra RECH; Mariana OLBERTTZ; Daniel Junior Moreira PAIVA; Adelizi Nataly RIBEIRO; Thais GIMENEZ; José Carlos Pettorossi IMPARATO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT The treatment of cavity carious lesions in anterior deciduous teeth is a frequent demand in the pediatric dentistry clinic, since the control of the disease in early childhood still presents itself as an inter-factor challenge in child health care. While the scientific evidence on the minimally invasive principles of approach in Dentistry is presented at an increasing level, the alternatives for restorative treatment in anterior deciduous teeth still face the low availability of reports that associate minimal intervention with the aesthetic needs inherent to the treatment. Thus, this article presents a series of cases in which direct restorations in composite resin, without removing carious tissue using polyvinyl matrices, were treatment alternatives for moderate and severe caries lesions in anterior deciduous teeth. It was observed, therefore, that the use of this artifact helped the rehabilitation of compromised dental elements with speed and satisfactory 50 result, suggesting that this is an appropriate approach for application in Pediatric Dentistry, 51 since it offers resistance, durability, besides providing aesthetics and functionality, it presents lower cost and agility as it eliminates the laboratory phase.